THE EFFECTIVENESS OF THE POWER OF TWO STRATEGY ON CRITICAL THINKING SKILLS HIGH SCHOOL STUDENT - Riana Putri; Anik Ghufron (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran)
KEEFEKTIFAN STRATEGI THE POWER OF TWO TERHADAP KECAKAPAN CRITICAL THINKING SISWA